Representaciones sociales en adultos mayores frente a los cuidados prestados por la institución “Hogar Nueva Vida”, un análisis desde la perspectiva de la calidad de vida. (2017)
The research makes an analysis of the relationship between; the representation of care, with the quality of life of the elderly; Belonging to the institution "Hogar Nueva Vida" located in the city of Bogotá. To do this, the research is based on a mixed approach, where two instruments are applied to eight older adults, institutionalized to collect information (semi-structured interview on care and quality of life, GENCAT® quality of life scale)